PELATIHAN SENI TEATER DI SURAKARTA : POTENSI, PERKEMBANGAN, DAN PENGELOLAAN - Makaf, Akhyar (Acintya, 2020)
ABSTRACT Theater Arts is widely taught in non-formal educational institutions such as studios, hermitage and extracurricular activities in formal schools. Its existence continues to grow as art education is realized to be an alternative media for the learning process. There came a number of Theater Arts training institutions in Surakarta. This research was conducted to examine the potential, development, and management of several training institutions that have a good reputation and have proven their presence in Surakarta. Qualitative research methods with analytic descriptive are used to analyze the training methods, curriculum, and management of training institutions that are used as research objects in order to see their potential and development. The results of this study can be used as a reference for anyone who is interested in developing non-formal educational institutions in the arts, especially Theater Arts. Based on this research, it can be concluded that the city of Surakarta as a City of Performing Arts, has the potential to be a location for the development of the Theater Arts training field. From the two objects of the training institution studied, the differences and variations in the training and management methods applied are described in accordance with the composition of the participants and the curriculum applied.Key words: theater arts, non-formal education, training methods, management.  ABSTRAK  Seni Teater banyak diajarkan dalam lembaga pendidikan non-formal seperti sanggar, padepokan dan kegiatan ekstrakurikuler di sekolah formal. Keberadaannya terus berkembang seiring disadarinya pendidikan seni sebagai media alternatif proses pembelajaran. Maka muncullah beberapa lembaga pelatihan Seni Teater di Surakarta. Penelitian ini dilakukan untuk mengkaji potensi, perkembangan, dan pengelolaan dari beberapa lembaga pelatihan yang sudah bereputasi cukup baik dan teruji keberadaannya di Surakarta. Metode penelitian kualitatif dengan deskriptif analitik digunakan untuk menganalisis metode pelatihan, kurikulum, dan pengelolaan lembaga-lembaga pelatihan yang dijadikan objek penelitian, guna melihat potensi dan perkembangannya. Hasil penelitian ini dapat digunakan sebagai rujukan bagi siapa pun yang tertarik untuk mengembangkan lembaga pendidikan non-formal di bidang seni, khususnya Seni Teater. Berdasarkan penelitian ini, dapat ditarik kesimpulan bahwa kota Surakarta sebagai Kota Seni Pertunjukan, berpotensi sebagai lokasi pengembangan bidang pelatihan Seni Teater. Dari dua objek lembaga pelatihan yang diteliti, tergambar perbedaan dan variasi metode pelatihan dan pengelolaan yang diterapkan sesuai dengan komposisi peserta dan kurikulum yang diterapkan. Kata-kata kunci : seni teater, pendidikan non-formal, metode pelatihan, pengelolaan.